An Epic Poem in Turkish From the Nineteenth Century - Nametak, Fehim (Prilozi za orijentalnu filologiju, 2017)
This paper presents a folk epic poem dastan in the Turkish language Which deals with the campaign of Husejin kapetan Gradaščević against the regular imperial army. The poem has been preserved in a codex from the beginning of the 19th century (it is contemporaneous with the events described in the poem) which is the property of Alija Nametak from Sarajevo. In the 20 stanzas of the poem, which has no great artistic value, many events in connection with the campaign of Husejin kapetan on Kosovo are described. The value of this dastan should therefore be sought in its documentary character. Husejin kapetan himself, as well as his followers, is not positively described; thus, one may infer that the poem was written by an anonymous soldier of the imperial army. Also, as the codex comes from Kosovo, the author was probably in Albanian.